The Power of Ideas: Some Remarks about Two Recent Books on the History of Medieval Political Thought - Nederman, Cary J. (Reti Medievali Rivista, 2020)
This essay discusses the historiography of Western medieval political thought, as reflected in Il pensiero politico medievale by Gianluca Briguglia and Il potere al plurale: Un profilo di storia del pensiero politico medievale by Roberto Lambertini and Mario Conetti. These two volumes propose vastly different approaches to the topic both in terms of chronology and focus, the first focusing mainly on texts, the other primarily on practices and institutions. Read in conjunction with one another, these books testify to the complexities involved in conceptualizing the emergence and development of political ideas in Europe between the fall of the Roman Empire in the West and the era of the Renaissance and the Reformation.